(Un)supported current tourism development in UNESCO protected site: The case of Old City of Dubrovnik - Ivana Pavlić; Ana Portolan; Barbara Puh (Economies, 2017)
The main purpose of this paper is to explore and determine perceptions of residents living in the United Nations Educational, Scientific and Cultural Organization (UNESCO) protected site Old City of Dubrovnik (OCD) towards tourism development. Uncontrolled tourism expansion has impact on local residents' life and on their (un)support for specific form of tourism development. Comprehension of residents' perceptions is crucial for realization of adequate tourism development and for mutual satisfaction of tourism demand and supply. Therefore, the aim is to test the model of residents' perceptions of economic, socio-cultural and environmental impacts of tourism on their (un)support for specific form of tourism development. To realize the purpose of this research, Cronbach alpha, explorative (EFC) and confirmatory (CFA) factor analysis, and structural equation modeling (SEM) were applied. The findings indicate that there is a direct relationship between residents who perceive positive and negative economic, socio-cultural and environmental impacts of tourism and their (un)support for tourism development. This paper points out the role and significance of the permanent residents' perceptions research concerning the issues that are related to the quality tourism development due to the high interaction between local residents, tourists and local tourism development especially in the areas under the protection of UNESCO.
Keywords: Z32; M31; 330; local residents' perceptions; tourism development; UNESCO protected site; Old City Dubrovnik (OCD); tourism impacts